The Application of the Morton Principles in Canada Steamship Lines Ltd v The King in Singapore Reconsidered - LOO, Wee Ling (Institutional Knowledge at Singapore Management University, 2016)
For the interpretation of clauses that purportto allow a contracting party, the proferens, to exclude or limit, or beindemnified against, liability that arises by reason of his or his agents’negligence, certain principles were laid down by the Privy Council in 1952 inCanada Steamship Lines Ltd v The King. Famously known as the ‘Mortonprinciples’ (named after Lord Morton who delivered the judgment of the PrivyCouncil) or the ‘Canada SS rules’ or guidelines, they prescribe a three-steptest to determine if these clauses effectively provide the protection sought bythe proferens. In Singapore, the Court of Appeal in Marina Centre Holdings PteLtd v Pars Carpet Gallery Pte Ltd elucidated the application of the principles.Two subsequent High Court decisions, however, did not appear to have appliedthe principles in like manner or with clarity. This article attempts to providea clearer understanding of how the Morton principles operate and to considertheir continued utility in Singapore. The writer concludes that while theprinciples serve a purpose in light of gaps in the UCTA, complexity inapplication would require judicial clarity and precision for their coherentuse, which itself presents a challenge. Additional problems, including theinability of the Morton principles to adequately fill the gaps in the UCTA, maymake reform attractive as a practical way forward. Obstacles to reform maymean, however, that it is premature to discard the Morton principles for now.